Time-series maps reveal widespread change in plant functional type cover across Arctic and boreal Alaska and Yukon. (1st May 2022) - Macander, Matthew J; Nelson, Peter R; Nawrocki, Timm W; Frost, Gerald V; Orndahl, Kathleen M; Palm, Eric C; Wells, Aaron F; Goetz, Scott J
Abstract: Widespread changes in the distribution and abundance of plant functional types (PFTs) are occurring in Arctic and boreal ecosystems due to the intensification of disturbances, such as fire, and climate-driven vegetation dynamics, such as tundra shrub expansion. To understand how these changes affect boreal and tundra ecosystems, we need to first quantify change for multiple PFTs across recent years. While landscape patches are generally composed of a mixture of PFTs, most previous moderate resolution (30 m) remote sensing analyses have mapped vegetation distribution and change within land cover categories that are based on the dominant PFT; or else the continuous distribution of one or a few PFTs, but for a single point in time. Here we map a 35 year time-series (1985–2020) of top cover (TC) for seven PFTs across a 1.77 × 10 6 km 2 study area in northern and central Alaska and northwestern Canada. We improve on previous methods of detecting vegetation change by modeling TC, a continuous measure of plant abundance. The PFTs collectively include all vascular plants within the study area as well as light macrolichens, a nonvascular class of high importance to caribou management. We identified net increases in deciduous shrubs (66 × 10 3 km 2 ), evergreen shrubs (20 × 10 3 km 2 ), broadleaf trees (17 × 10 3 km 2 ), and conifer trees (16 × 10 3 km 2 ), and net decreases in graminoids (−40 × 10 3 km 2 ) and light macrolichens (−13 × 10 3 km 2 ) over the full map area, with similar patterns across Arctic, oroarctic, and boreal bioclimatic zones. Model performance was assessed using spatially blocked, nested five-fold cross-validation with overall root mean square errors ranging from 8.3% to 19.0%. Most net change occurred as succession or plant expansion within areas undisturbed by recent fire, though PFT TC change also clearly resulted from fire disturbance. These maps have important applications for assessment of surface energy budgets, permafrost changes, nutrient cycling, and wildlife management and movement analysis.